Uma an??lise jur??dica, econ??mica e comportamental acerca da legaliza????o dos ???jogos de azar??? no Brasil - Scalea, Jos?? Augusto (2017)
This work aims to analyse the legal, economic and social impacts of the proposals for legalisation of the commercial exploitation of gaming in Brazil. This analysis was done using the tools and concepts of law and economics primarily, by the optics of the so-called economic analysis of law, but also counts with traces of psychology on some behavioral issues. The benefits and social costs were taking into account the current legislative proposals in the brazilian legislative power on the subject matter. Suggestions have been made for improvements in the law projects and observations about what the legislator really wants with the alleged legalisation. The cost-benefit analysis points to the feasibility of legalisation with the potential for generating employment and income for the Brazilian population as well as a possible increase in national tourism. The social costs to be supported apparently will be inferior to the experienced benefits, which in economic reading suggests legalisation. The use of controlled experiments is the main suggestion that is made to the legislator to collect more data on the actual impacts of the commercial exploitation of the gaming in Brazil.